Development of computational fluid dynamics (CFD) models for heat recovery system in buildings (ANSYS FLUENT) - Kwa, Yin En (2016)
Heating, ventilating and air-conditioning (HVAC) accounts for approximately 50% of the power consumption of most buildings. [3] Ever evolving and advancing, and with a growing population, HVAC systems plays an important part in providing a cooler environment and thus comfort for Singaporean’s highly urbanized everyday life. As such, due to the overwhelming energy usage of the HVAC system much attention is placed to reduce the energy consumption of it. Also, it proves as a long term solution to this advancing city. Therefore, energy recovery ventilator (ERV) is one of the solution to reducing energy consumption of HVAC systems. This project studies if the usage of a membrane-based type of energy recovery ventilator (ERV) in a dedicated outdoor air system (DOAS) for hot and humid climate condition like Singapore would reduce the energy consumption. By using the simulation program ANSYS Fluent, this project would simulate a layer of the counter-flow two-way airflow core of a heat exchanger to investigate the heat transfer between this 2 air flow. The three parameters to be varied in this study are inlet velocities, inlet temperature and inlet relative humidity. By varying the different parameters and studying the changes in temperature and moisture content of the model, the study would be able to investigate the heat transfer and moisture transfer between the airflows and thus able to devise ways to improve the efficiency of the membrane-based ERV.